Construction the linear codes in PG (1, 31) - Easa, Ahmed Khallaf; Al-Seraji, Najm Abdulzahra Makhrib (Iraqi Journal of Science, 2023)
The goal of this paper is to construct the linear code, and its dual which corresponding to classification of  projective line PG(1,31), we will present Some important results of coding theory, the generator matrix of every linear code in PG(1,31) is found,  A parity check  matrix is  also found . The mathematical programming language GAP was a main computing tool .